Social responsibility in the behavior of organizational citizenship on the basis of the organizational justice of employees at the University of Al-Aqsa variable mediator - Al-derawi, Ayman Hassan (Journal of Economic, Administrative and Legal Sciences, 2019)
The aim of the study is to examine the relationship between social responsibility and the behavior of organizational citizenship in the employees of Al-Aqsa University, taking into account the need of Al-Aqsa University to create a state of organizational justice as an intermediate variable. The descriptive analytical method was used by applying the random sampling method of 175 individuals from a community of 320 administrative staff working at Al-Aqsa University in the Gaza Strip. Among the most important results of the Research findings was a positive correlation between all dimensions of social responsibility (training, development, human rights, health and public safety, balance between work and life and diversity in the work environment) and the organizational citizenship behavior of Al-Aqsa University employees. Social responsibility and organizational citizenship behavior. The most important recommendations are: to increase the awareness of management and employees of the importance of social responsibility as a means of achieving the university’s organizational justice.